Bioentrepreneurship avenues and opportunities in potato - Singh, Rajender; Sood, Salej; Mangal, Vikas; Kumar, Vinod; Singh, Brajesh (Indian Horticulture, 2024)
The ICAR-Central Potato Research Institute has been instrumental in development of 70 native potato varieties and has also contributed to popularize potato cultivation as well as utilization under various agro-climatic regions in the country. Following these scientific advances, India has emerged as the world’s secondlargest potato producer, accounting for around 12% of the crop’s total production. The potato industry is contributing significantly to the growth of entrepreneurship, particularly in the processing and seed industries. The potato crop has enormous potential to improve the country’s food and nutritional security. Since the beginning of the last decade, the Institute has taken a proactive role in promoting intellectual property rights and licensing institute’s technologies to young people and other individuals working in the seed and processing industries. Commercialization of institute’s technologies is critical to fostering an entrepreneurial culture in the country.